2006
DOI: 10.1182/blood-2006-03-007146
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the JAK2 G1849T (V617F) mutation occurs in a lymphomyeloid progenitor in polycythemia vera and idiopathic myelofibrosis

Abstract: The JAK2 V617F mutation has recently been described as an essential oncogenic event associated with polycythemia vera (PV), idiopathic myelofibrosis (IMF), and essential thrombocythemia. This mutation has been detected in all myeloid lineages but has not yet been detected in lymphoid cells. This raises the question whether this molecular event occurs in a true lymphomyeloid progenitor cell. In this work, we studied the presence of the mutation in peripheral

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
117
1
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(140 citation statements)
references
References 26 publications
16
117
1
6
Order By: Relevance
“…26,28 In contrast, p5% of patients with chronic myelomonocytic leukemia, myelodysplastic syndrome or de novo acute myeloid leukemia (AML) harbor this particular mutation. 29,30 JAK2V617F has been identified in the hematopoietic stem cell compartment, 31 and has been demonstrated in non-myeloid cells including B and T lymphocytes, 32 as well as natural killer cells. 33 JAK2V617F recapitulates some of the key in vitro biological characteristics of MPDFfor instance, it increases the survival of cytokine-dependent cells cultured in the absence of cytokines, 21,23,24 and appears to promote ex vivo EEC growth from PV progenitor cells.…”
Section: Jak2v617f Eramentioning
confidence: 99%
“…26,28 In contrast, p5% of patients with chronic myelomonocytic leukemia, myelodysplastic syndrome or de novo acute myeloid leukemia (AML) harbor this particular mutation. 29,30 JAK2V617F has been identified in the hematopoietic stem cell compartment, 31 and has been demonstrated in non-myeloid cells including B and T lymphocytes, 32 as well as natural killer cells. 33 JAK2V617F recapitulates some of the key in vitro biological characteristics of MPDFfor instance, it increases the survival of cytokine-dependent cells cultured in the absence of cytokines, 21,23,24 and appears to promote ex vivo EEC growth from PV progenitor cells.…”
Section: Jak2v617f Eramentioning
confidence: 99%
“…Erythrocytes were removed by sedimentation with Dextran (Sigma-Aldrich, St Louis, MO, USA). Granulocytes were further fractionated on a Biocoll density gradient centrifugation (1077 g per cm 3 ). Total blood DNA or DNA isolated from granulocytes was purified with a Qiagen kit (Qiagen, Courtabeouf, France).…”
Section: Patients and Genotypingmentioning
confidence: 99%
“…1 MPDs are hematological diseases characterized by a clonal proliferation of one or several myeloid lineages 2 arising from the transformation of a multipotent hematopoietic stem cell by an oncogenic event such as Bcr-abl fusion protein kinase, mutated Janus kinase JAK2 V617F or thrombopoietin receptor (TPO-R) MPL W515L that induces constitutive signaling. [3][4][5] However, approximately 40% of patients with ET and PMF do not present such mutations, [6][7][8][9][10][11] and genetic analysis is still under progress to elucidate the responsible oncogenic events.…”
Section: Introductionmentioning
confidence: 99%
“…The development of more sensitive examination methods by several independent groups, however, revealed that at least in some patients small fractions of clonal B-, T-lymphocytes and natural killer cells do actually carry the JAK2V617F mutation. 12,15,[131][132][133][134] Notably, all disease entities, PV, ET and PMF, showed lymphocyte involvement although this phenomenon was more common in PMF and PV. Therefore, it was concluded that the earliest affected cell must be a pluripotent non-committed stem cell with the potential for both myeloid and lymphoid differentiation.…”
Section: Jak2 Mutationsmentioning
confidence: 99%